2015
DOI: 10.1016/j.jcomdis.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Co-verbal gestures among speakers with aphasia: Influence of aphasia severity, linguistic and semantic skills, and hemiplegia on gesture employment in oral discourse

Abstract: The use of co-verbal gestures is common in human communication and has been reported to assist word retrieval and to facilitate verbal interactions. This study systematically investigated the impact of aphasia severity, integrity of semantic processing, and hemiplegia on the use of co-verbal gestures, with reference to gesture forms and functions, by 131 normal speakers, 48 individuals with aphasia and their controls. All participants were native Cantonese speakers. It was found that the severity of aphasia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 67 publications
(97 reference statements)
4
36
0
Order By: Relevance
“…Previous studies on PWA's gesture use have suggested that PWA tend to produce a greater number of gestures per word than healthy speakers (e.g., Kong, Law, Wat, et al, 2015;Wat, 2013). Some investigators also argued that the semantic complexity of gestures was lower in PWA (e.g., Ahlsén & Schwarz, 2013).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Previous studies on PWA's gesture use have suggested that PWA tend to produce a greater number of gestures per word than healthy speakers (e.g., Kong, Law, Wat, et al, 2015;Wat, 2013). Some investigators also argued that the semantic complexity of gestures was lower in PWA (e.g., Ahlsén & Schwarz, 2013).…”
Section: Discussionmentioning
confidence: 92%
“…This observation supported the sketch model (de Ruiter, 2000) and provided evidence for independent deficits of gesture and verbal production. Recent studies by Kong, Law, Wat, and Lai (2015) and Wat (2013) further corroborated the sketch model by concluding that the rate of gesture use among 48 PWA (with preserved nonverbal semantic abilities) was higher than that of their controls, and a higher proportion of PWA used coverbal gestures as compared with the control counterparts. Moreover, although the presence of hemiplegia in PWA did not affect their rate of using gestures, higher aphasia severity, weaker linguistic skills (as reflected by fewer complete and simple sentences), and lower degree of verbal semantic processing integrity were found to associate with an increased proportion of coverbal gesture use.…”
Section: Aphasia and Gesture Usementioning
confidence: 88%
See 2 more Smart Citations
“…Subsequent analyses in terms of the quantity of gestures and how their forms and functions are affected by aphasia can be conducted; this would allow a better understanding of whether and how speakers may employ gestures to enrich spoken discourse. A recent study utilizing a subset of the data bank to answer the above questions has been reported (Kong, Law, Wat, & Lai, 2015). 2.…”
Section: Potential Contribution To Research In Linguistic Psycholingmentioning
confidence: 99%